Microbial and metabolic profile of achlorhydric stomach: comparison of pernicious anaemia and hypogammaglobulinaemia. - Borriello, S P (1985)
The microbial flora and some of its metabolites and enzymes in the stomach were compared in patients with achlorhydria, pernicious anaemia, and primary hypogammaglobulinaemia and in patients with dyspepsia with normal gastric acidity. Detailed analysis of the flora of the gastric juice and of the mucosa from the antrum, body, and fundus in six patients with hypogammaglobulinaemia (mean pH 8.2), seven patients with pernicious anaemia (mean pH 7.3), and five patients with dyspepsia (mean pH 1.9) yielded 22 different genera of bacteria, mainly from the patients with achlorhydria, the most common being streptococci, micrococci, staphylococci, veillonella, and lactobacilli. A similar flora was found associated with the mucosa at all three sites. Various metabolites were also looked for. beta Glucoronidase and C14 lipase were found in patients with hypogammaglobulinaemia but not in those with pernicious anaemia or dyspepsia. Volatile fatty acids were not found. Relatively high concentrations of ethanol were found in the patients with hypogammaglobulinaemia compared with those with pernicious anaemia (p = 0.02). Similar concentrations of dimethylamine were found in all three groups, but the concentrations of trimethylamine were much higher in patients with pernicious anaemia and hypogammaglobulinaemia. The high concentrations of some microbial enzymes and ethanol differentiated the group with hypogammaglobulinaemia from the rest, and these may bear some relation to the high incidence of gastric cancer in patients with hypogammaglobulinaemia.